THE EFFECT OF HEXAGON FRAUD ON FINANCIAL STATEMENT FRAUD (STUDY OF BASIC MATERIAL SECTOR COMPANIES IN 2020-2022) - Hakim, Mohamad Zulman; Hesti Erviani Zulaecha; Eko Sudarmanto; Liyusabyte Ali; Deniza Mukti; Khoirunnisa Siregar (ZILLZELL MEDIA PRIMA, 2024)
Fraud cases have increased from year to year and the most detrimental is fraudulent financial statements and causing losses for the company and for user’s financial statements. This research aims to analyze the deep hexagon fraud factors detecting financial statement fraud in Basic Material sector companies registered in Indonesian Stock Exchange (BEI) for the 2020-2022 period. The population used was 93 companies basic materials sector listed on the Indonesian Stock Exchange. Purposive sampling method is the sampling method used in this research. The sample meeting the research criteria are 31 basic material companies with total observations of as many as 93. The data analysis method uses the logistic regression method with the help of an application EViews to carry out data testing. The results of this research are expected to provide better understanding of the factors that influence fraud reports on financial sector Basic Materials Company. Apart from that, the results of this research can also provide insights for companies and regulators in improving internal controls, actions prevention, and detection against financial statement fraud.